Impacts of current global economic crisis on Asia's labor market - Phu Huynh; Steven Kapsos; Kee Beom Kim; Gyorgy Sziraczki (Asian Development Bank Institute (ADBI), 2010)
The paper investigates the labor market and social impacts of the global financial and economic crisis in Asia and the Pacific as well as national policy responses to the crisis. It draws on recent macroeconomic, trade, production, investment, and remittances data to assess the employment and social consequences of the crisis, including falling demand for labor, rising vulnerable and informal employment, and falling incomes and their related pressures on the working poor. The paper provides some projections of the impact on unemployment, vulnerable employment, working poverty, and labor productivity in the region in 2009. It demonstrates that labor market recovery is likely to lag behind output growth, based on the experience of Asian labor markets following the 1997 Asian financial crisis. The paper underscores some policy options that are likely to have positive outcomes toward generating employment and boosting aggregate demand, improving social protection and welfare on the basis of decent work principles, and promoting a sound and sustainable economic and labor market recovery.
Keywords: E24; I30; J08; J20; 330; Wirtschaftskrise; Beschäftigungseffekt; Arbeitsmarktpolitik; Asien